Delayed-onset effect of clofarabine in the treatment of an adult patient with acute myeloid leukemia. (21st February 2019) - Walchack, Robert; Cumpston, Aaron; Vos, Jeffrey; Kanate, Abraham S
Abstract: Purpose: A delayed-onset effect of clofarabine in the treatment of an adult patient with acute myeloid leukemia (AML) is reported. Summary: A 44-year-old African-American man with pancytopenia was transferred to an academic medical center for evaluation. His medical history included bipolar depression, gynecomastia, and HIV infection (diagnosed 5 years prior) for which he was being treated with atazanavir, emtricitabine-tenofovir, and ritonavir. He was diagnosed with AML with 60% myeloblasts found during bone marrow biopsy. He had primary refractory disease after induction chemotherapy treatment. His disease was refractory to subsequent therapy with high-dose cytarabine and then etoposide and mitoxantrone. The patient then underwent treatment with granulocyte-colony stimulating factor-primed clofarabine and cytarabine (G-CLAC). At blood count recovery, he was diagnosed with refractory disease, with 17% blasts in peripheral blood and was subsequently discharged home on hospice 38 days after G-CLAC and 19 days after the last dose of filgrastim. He arrived at the outpatient clinic 79 days after G-CLAC chemotherapy with significantly improved blood counts. Two weeks later, a bone marrow biopsy confirmed complete remission with incomplete hematologic recovery. Conclusion: A patient with relapsed AML achieved a delayed response to clofarabine at least 38 days after treatment.